Morphometric Studies on The Tarsal Bones of Blue Bull (Boselaphus tragocamelus) - Bharti, Sanjay Kumar; Singh, lshwer; Dhote, Balwinder Singh; Choudhary , Om Prakash; Mrigesh, Meena (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
A study was carried out on the tarsal bones of blue bull. The tarsus of blue bull consisted of five bones i.e., tibial tarsal (Astragalus), fibular tarsal (Oscalcis), fused central and fourth tarsal (Scaphocuboid), first tarsal (Cunciformparvum) and second and third tarsal fused (Cuseiform magnum).The average height and breadth of tibial tarsal was 6.81 ±0.01 cm and 3.84±0.01 cm, respectively. The fibular tarsal was the longest, elongated bone of the tarsus and flattened from side to side with an average height and breadth 12.00±0.01 cm and 3.72±0.01 cm, respectively. The central and the fourth tarsalswere fused together to form a large single bone. The average height and breadth for central and fourth fused tarsal was 2.54±0.01 cm and 5.11 ±0.01 cm, respectively. The first tarsal was a quadrilateral piece of bone placed at the postero-internal part of the tarsus. The length and maximum breadth of first tarsal was 2.14±0.01 cm and 3.32±0.01 cm, respectively. The second and third fused tarsal was a small plate of bone having length and breadth of second and third fused tarsal 1 .68±0.01 cm and 3.34±0.01 cm, respectively.